Evaluation of Pharmacobezoar Formation from Suspensions of Spray-Dried Amorphous Solid Dispersions: An MRI Study in Rats - Hannes Gierke; Susan Mouchantat; Sabine Berg; Michael Grimm; Stefan Hadlich; Marie-Luise Kromrey; Thomas Nolte; Teresa Pfrommer; Vincent Rönnpagel; Adrian Rump; Kerstin Schaefer; Ann-Cathrin Willmann; et al. (MDPI AG, 2023)
Spray-dried amorphous solid dispersions of new chemical entities and pH-dependent soluble polymer hydroxypropyl methylcellulose acetate succinate (HPMC-AS) were found to form solid agglomerates in the gastrointestinal tract of rodents after oral administration. These agglomerates, referring to descriptions of intra-gastrointestinal aggregated oral dosage forms termed pharmacobezoars, represent a potential risk for animal welfare. Previously, we introduced an in vitro model to assess the agglomeration potential of amorphous solid dispersions from suspensions and how it can be reduced. In this work, we investigated if the in vitro effective approach of viscosity enhancement of the vehicle used to prepare suspensions of amorphous solid dispersions could reduce the pharmacobezoar formation potential following repeated daily oral dosing to rats as well. The dose level of 2400 mg/kg/day used in the main study was determined in a dose finding study carried out in advance. In the dose finding study, MRI investigations were carried out at short time intervals to gain insights into the process of pharmacobezoar formation. Whereas MRI investigations underlined the importance of the forestomach for the formation of pharmacobezoars, viscosity enhancement of the vehicle reduced the incidence of pharmacobezoars, delayed the onset of pharmacobezoar formation and reduced the overall mass of pharmacobezoars found at necropsy.